Efficacy of bio-control agents and fungicides in the management of wilt of pigeon pea - RAM, HUKMA; PANDEY*, R.N. (Indian Phytopathology, 2011)
Three bioagents viz., Trichoderma viride, Pseudomonas fluorescens and P. aeruginosa and seven fungicides weretested in vitro and in pots against Fusarium udum, the causal agent of wilt of pigeonpea. T. viride completely checked themycelial growth of F. udum in dual culture. Bacterial bioagents also significantly reduced the growth of the pathogen. Amongthe fungicides, carbendazim (500 Î¼g ml-1), difenconazole (100 Î¼l ml-1), hexaconazole (200 Î¼l ml-1) and combi product of captan+ hexaconazole (250 Î¼g ml-1), and carbendazim + mancozeb (500 Î¼g ml-1) completely inhibited the mycelial growth of thepathogen. In pot culture studies, significantly minimum (13.81 %) incidence of wilt was observed in combined seed treatmentof metiram (0.1%) + T. viride which was at par with T. viride alone which showed 20.26 per cent incidence as compared tomaximum (52.23 %) wilt incidence in control.